IMPLEMENTATION OF CSR IN BENGKULU AFTER THE ISSUANCE OF THE BENGKULU GOVERNOR'S DECREE NUMBER: P.127.DINSOS. OF 2018 CONCERNING THE ESTABLISHMENT OF THE CSR FORUM OF BENGKULU PROVINCE - Difo Pradipta; Slamet Muljono; Emelia Kontesa (Universitas Bengkulu, 2021)
CSR is an element in improving people's welfare. Through the establishment of a CSR Forum which was established based on the Bengkulu Governor's Decree Number: P.127.Dinsos. In 2018 concerning the Establishment of the Bengkulu Province CSR Forum, the Regional Government seeks to increase the participation of every company in Bengkulu. However, the results have not been effective, this is because the formation of this forum was not accompanied by the authority and mechanism in the form of a Governor Regulation. Theimpact is that CSR implementation in Bengkulu Province is small and not focused. The problem in this research is how the implementation of CSR after the issuance of the Bengkulu Governor's Decree Number: P.127.Dinsos. 2018 concerning the Establishment of the Bengkulu Province CSR Forum and What Are the Obstacles in the implementation of the CSR forum. This type of research is empirical, data sources obtained from interviews, documents, as well as literature and legislation relevant to the research. The result of thisresearch is the finding of a 16% percentage of the participation rate of companies in Bengkulu, from a total of 196 companies in Bengkulu, only 33 companies registered by the CSR Forum have distributed CSR. The rest of this company never reported the distribution of CSR. This is very inconsistent with the Utilities Theory because large companies in Bengkulu Province have not contributed too much to the Environment and Society, and are still focused on Company Profits only. Furthermore, in the second discussion it was also conveyed that several obstacles were experienced by the CSR Forum, among others: The government has not yet embraced the forum in relation to companies, There is no Regulation on Implementation Mechanism in the Investment Law and the TDP Law, the Report Submission Mechanism is not Clearly, the absence of basic technical rules for implementing CSR reporting, absence of punishments and sanctions from the local government to companies for distributing CSR.